Pengaruh Motivasi Intrinsik Terhadap Prestasi Belajar Siswa pada Mata Pelajaran Bahasa Arab Kelas V di MI Al Azkia Tenjolaya Bogor - Linda Urpatullia; Ima Rahmawati; Hana Lestari; Zulfikar Ismail (Reslaj : Religion Education Social Laa Roiba Journal, 2021)
The purpose of this study was to determine the effect of intrinsic motivation on student achievement in Arabic class V at MI Al Azkia Tenjolaya Bogor. This study used a quantitative approach with a sample of 39 respondents using non probability sampling technique with saturated samples. Retrieval of data used questionnaires, non-participant observation and documentation. The data analysis technique used is simple linear regression using SPSS 20.0 application. Based on the results of the simple linear regression test, it was obtained a significant value of 0.000 <0.05, it can be concluded that there is a positive and significant influence between intrinsic motivation on learning achievement. It is demonstrated that the increasingly strong influence of the intrinsic, then of the learning achievement that generated by student will further increase.